A Comparison of Scientific and Engineering Criteria for Bayesian Model Selection - Heckerman, David; Chickering, Max (1996)
For each possible model m, we define the random (vector) variable Θ m whose values correspond to the possible values of the parameters for m. We encode our uncertainty about Θ m using the probability distribution p(Θ m jm). In this paper, we assume that p(Θ m jm) is a probability density function.
Tools and Algorithms for the Construction and Analysis of Systems (TACAS '07)